Ruby red herring : an Avery Ayers antique mystery - Gardner, Tracy (Crooked Lane, 2021)
"After her parents' deaths, Avery Ayers takes over the family business ... Now living back at home with her younger sister Tilly and their newly moved-in eccentric Aunt Midge and her Afghan hound, Avery's life is filled with jewels, tapestries, paintings, and rare finds. But their world is rocked when Avery learns that the theft of a priceless ruby may be connected to her parents' demise"--